The use of zein in the controlled release of poorly water-soluble drugs - Tran, Phuong H.L.; Duan, Wei; Lee, Beom Jin; Tran, Thao T.D. (International Journal of Pharmaceutics, 2019)
Although zein is a natural protein derived from corn, it has attracted much interest in pharmaceutical and biomedical sciences. Recent remarkable investigations on the use of zein in controlled drug delivery have contributed both important knowledge and potential applications of various products, particularly in the delivery of poorly water-soluble drugs. Zein has also been approved by the Food and Drug Administration for oral delivery. Substantial research has been performed to demonstrate the roles and promise of materials containing zein for pharmaceutical applications. Significant efforts have focused on the biodegradable and hydrophobic properties of zein and on technology using zein as a nanocarrier specifically for nanomedicine. However, important issues concerning the use of zein in technical advances and in the development of poorly water-soluble drugs must be addressed in order to use zein in translational research. This review aims to focus on the classification of potential approaches for using zein in the controlled release of poorly water-soluble drugs and to discuss recommended techniques for creating high-quality products from zein.
Keywords: Delayed-Action Preparations; Drug Compounding; Excipients; Microspheres; Nanoparticles; Solubility; Water; Zein; Controlled drug release; Hydrophobic property; Nanocarrier; Poorly water-soluble drug; Zein